2021
DOI: 10.1186/s13071-021-04908-x
|View full text |Cite
|
Sign up to set email alerts
|

Entomological characterization of Aedes mosquitoes and arbovirus detection in Ibagué, a Colombian city with co-circulation of Zika, dengue and chikungunya viruses

Abstract: Background Dengue, Zika and chikungunya are arboviruses of significant public health importance that are transmitted by Aedes aegypti and Aedes albopictus mosquitoes. In Colombia, where dengue is hyperendemic, and where chikungunya and Zika were introduced in the last decade, more than half of the population lives in areas at risk. The objective of this study was to characterize Aedes spp. vectors and study their natural infection with dengue, Zika and chikungunya in Ibagué, a Colombian city an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
(58 reference statements)
1
16
0
5
Order By: Relevance
“…We found that wealthier households where occupants displayed higher knowledge of arboviruses were associated with lower Aedes density. Household wealth is widely known to affect mosquito vector density, potentially through better access to mosquito control methods [ 22 , 26 , 34 , 43 ], and the effect of knowledge about mosquito vectors and arboviruses on household mosquito vector density and arboviral disease risk has also been the subject of many studies [ 27 , 44 , 45 ]. We also found major effects of presence of decorative vegetation and landscape elements around the household.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that wealthier households where occupants displayed higher knowledge of arboviruses were associated with lower Aedes density. Household wealth is widely known to affect mosquito vector density, potentially through better access to mosquito control methods [ 22 , 26 , 34 , 43 ], and the effect of knowledge about mosquito vectors and arboviruses on household mosquito vector density and arboviral disease risk has also been the subject of many studies [ 27 , 44 , 45 ]. We also found major effects of presence of decorative vegetation and landscape elements around the household.…”
Section: Discussionmentioning
confidence: 99%
“…Identified specimens were then stored in RNAlater (Thermo Fisher Scientific, Waltham, MA, USA) and transported to a laboratory for subsequent processing and molecular analysis for virus detection; the results of these analyses are to be presented in separate papers (e.g. [ 34 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Also, studies of natural infection in Aedes mosquitoes in central departments of the country in 2016 reported high rates of DENV-2 infection in A. aegypti, possibly associated with the epidemic that occurred during that year (Pérez-Castro et al, 2016;Ruiz-López et al, 2016;Gómez-Palacio et al, 2017;Pérez-Pérez et al, 2017). Similarly, reports of infection in Aedes during 2018 and 2019 showed DENV-1 infections related to the latest outbreak in Colombia (Martínez et al, 2020;Carrasquilla et al, 2021). Given this scenario, our findings on the frequency of infection in A. aegypti could be associated with this national trend and reveal the predominant serotype transition from serotype DENV-1 to DENV-2 in all departments, suggesting that the latter serotype could be the cause of the next outbreak in the country.…”
Section: Discussionmentioning
confidence: 74%
“…In recent years, a gradual decrease in the notification of Chikungunya and Zika cases has been observed (Instituto Nacional De Salud, 2020, 2022, with a low incidence in 2020 and 2021 (0.3-0.5 cases per 100.000 inhab) for both arboviruses. The reduced circulation of these arboviruses may be associated with low rates of susceptible population turnover and reintroduction (Carrasquilla et al, 2021), which limits the circulation of these viruses in humans and Aedes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation